Internet of Things based Heart Rate Monitoring and Alert System - Md Shah, Wahidah; Yaakob, Mohd Hazman; Harum, Norharyati; Hassan, Aslinda; Othman, Mohd Fairuz Iskandar; A Hamid, Isredza Rahmi (Universiti Teknikal Malaysia Melaka (utem), 2020)
Heart rate analysis provides vital information of the present condition of the human body and become one of the important indicators of health. Manual monitoring method no longer efficient since requires physical access from the medical staff. Thus, a system that provides a real-time monitoring and alert is needed. In this paper, we develop a heart rate alert system that is usable for medical officer and patients. The system measures the variation of the tissue blood flow rate by means of a photo transmitter and detector through fingertip known as photoplethysmography (PPG). The detected signal is passed through active low pass filter and then amplified by a two stages high gain amplifier. The amplified signal is feed into the microcontroller to process the heart rate. Then, the heart rate reading is transferred to a running web server for dashboard views for monitoring. For alerting medical officer, the system able to trigger and send a notification message through Telegram platform in the occurrences of abnormal heart rate reading. Mean of reading differences and response time testing were carried out for the performance testing of the system. Overall, the system is capable in providing an alternative method for the medical staff to monitor and get alert about the heart rate of the patients. This system can be deployed in hospitals or used by heart disease patients to monitor their heart rate condition from time to time.